Curriculum and Competency Evaluation in Respiratory Therapy Entry-to-Practice Programs. - Jones, Thomas D.; Willis, L. Denise; Spray, Beverly J.; Berlinski, Ariel (Respiratory Care, 2023)
Background: Essential skills for respiratory therapists extend beyond the traditional scope of therapy. Respiratory therapists are expected to communicate effectively, deliver bedside education, and practice within interprofessional teams. Respiratory therapy entry-to-practice program accreditation standards require evaluation of student competence in communication and interprofessional practice. This study aimed to determine if entry into practice programs include curriculum and competency evaluation for oral communication, patient education, telehealth, and interprofessional activities. Methods: The primary objective was to identify the curriculum and method of competency evaluation. The secondary objective was to compare degree programs. Directors of accredited respiratory therapy programs were invited to complete an anonymous survey with regard to degree program type, oral communication, patient education, learning strategies, telehealth, and interprofessional activities. Degree programs were classified as associate's of science 2 year, associate's of science < 2 year, or bachelor's of science. Results: Of 370 invited programs, respondents in 136 programs (37%) completed the survey. Oral communication competence was evaluated by 82%. Patient education curriculum and competency evaluation were reported by 86% and 73%, respectively. Telehealth was rarely included or evaluated. Interprofessional activities were included by 74%, of whom 67% evaluated competency. Bachelor's of science programs were more likely to include a specific patient education course (P = .004), evaluate oral communication competency with unpaid preceptors (P = .036), and evaluate interprofessional competence through formal interprofessional programs (P = .005). Associate's degree 2-year programs used laboratory proficiency for patient education competency evaluation more often than other programs (P = .01). associate's of science < 2-year programs were more likely to include simulation experiences that involved motivational interviewing (P = .01). Conclusions: Differences exist among program types for curriculum and competency evaluation. Telehealth was rarely included or evaluated at any degree level. Programs should evaluate the need for enhanced patient education and telehealth instruction.